Utilities Included: Split Incentives in Commercial Electricity Contracts - Katrina Jessoe; Maya Papineau; David S. Rapson (Center for Economic Studies and ifo Institute (CESifo), 2019)
This paper quantifies a tenant-side “split incentives” problem that exists when the largest commercial sector customers are on electricity-included property lease contracts causing them to face a marginal electricity price of zero. We use exogenous variation in weather shocks to show that the largest firms on tenant-paid contracts use up to 14 percent less electricity in response to summer temperature fluctuations. The result is retrieved under weaker identifying assumptions than previous split incentives papers, and is robust when exposed to several opportunities to fail. The electricity reduction in response to temperature increases is likely to be a lower bound when generalized nationwide and suggests that policymakers should consider a sub-metering policy to expose the largest commercial tenants to the prevailing retail electricity price.
Keywords: D22; L14; Q51; 330; electricity; principal-agent problem; split incentive; contracts